1973
DOI: 10.1002/chin.197331317
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: UMSETZUNG DES TRICHLORPHOSPHAZOPERCHLORAETHANS MIT AMMONIUMCHLORID

Abstract: Trichlorphosphazoperchloräthan (I) wird ohne Lösungsmittel in Gegenwart katalytischer Mengen Aluminiumchlorid erhitzt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
1996
1996

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The synthesis of the title compound, namely the 1,3,2λ 5 -diazaphosphete F has been claimed in 1973; however, soon after Glemser demonstrated that it was in fact a mixture of 6-membered rings G and H . Although the mechanism of the reaction has not been elucidated, it seemed quite possible that the observed products G and H resulted from a disproportionation of the 4-π-electron 4-membered ring F , arguing again for the high instability of the 4-π-electron 4-membered heterocycles.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of the title compound, namely the 1,3,2λ 5 -diazaphosphete F has been claimed in 1973; however, soon after Glemser demonstrated that it was in fact a mixture of 6-membered rings G and H . Although the mechanism of the reaction has not been elucidated, it seemed quite possible that the observed products G and H resulted from a disproportionation of the 4-π-electron 4-membered ring F , arguing again for the high instability of the 4-π-electron 4-membered heterocycles.…”
Section: Introductionmentioning
confidence: 99%